A 6-year-old Female With Frequent Vomiting and Carpopedal Spasm: 6-Year-Old Female with Carpopedal Spasm - Marzani, Seyedeh Fatemeh (Journal of Pediatric Nephrology, 2025)
Background and Aim: Gitelman syndrome (GS) is a rare tubulopathy with an autosomal recessive inheritance pattern. Mutations in the thiazide-sensitive Na-Cl transporter gene lead to hypokalemia, metabolic alkalosis, and hypomagnesemia. Case Presentation: In this case report, we introduced a 6-year-old female who presented with urinary tract infection symptoms and frequent vomiting. She suffered from carpopedal spasm when blood sampling was done. At presentation, she had acute respiratory alkalosis with complete metabolic compensation, mild hypokalemia, and hypomagnesemia. After discharge, further studies, including genetic testing, were conducted, which identified an SCL12A3 mutation—a homozygous pathogenic variant—that confirmed the diagnosis of Gitelman syndrome. Oral supplementation of potassium and magnesium was initiated for treatment. Conclusion: The diagnosis of GS can be easily missed. Clinical Suspicion is the first step toward confirming a diagnosis.